Microstructure Examinations in Corners of the Low-Carbon Steel Slabs from Continuos Caster Machine - Kwinta G. (Archives of Metallurgy and Materials, 2016)
The exposed selvedge layers in slabs cast by the continuous process should be free from surface defects, which in most cases appear in the form of cracks on the casting surface and run to its interior. In addition to the parameters of the casting process, the occurrence of such defects depends on the chemical composition of cast steel, on the segregation of surface active elements and formation of the precipitates of carbides, nitrides and other phases. Due to the frequent occurrence of defects in corners of the slabs, non-destructive testing was performed on the mechanically cleaned surfaces of slabs. The test material was low-carbon API(American Petroleum Institute API 5L standard) steel micro alloyed with Nb and Ti designed for the production of pipes to handle gas, oil and other liquid and gaseous fuels. Despite the use of different methods of inspection, i.e. ultrasonic, magnetic particle and penetrant, cracks were not traced in the examined material. Then, from the corners of the examined slabs, specimens were cut out for metallographic examinations. The main purpose of these examinations was to disclose the presence of possible cracks and micro cracks on the surfaces transversal and longitudinal to the direction of casting. At the same time, studies were conducted to establish the number and morphology of non-metallic inclusions in selvedge layers of the slab corners and axis. Additionally, hardness of the slabs was measured. The conducted studies revealed only some minor differences in the slab hardness along its axis (130 ÷ 135 HB) and in selvedge layers (120 ÷ 123 HB).